Using Next-Generation Sequencing to Identify a Mutation in Human MCSU that is Responsible for Type II Xanthinuria - Yunan Zhou (Cellular Physiology and Biochemistry, 2015)
Background: Hypouricemia is caused by various diseases and disorders, such as hepatic failure, Fanconi renotubular syndrome, nutritional deficiencies and genetic defects. Genetic defects of the molybdoflavoprotein enzymes induce hypouricemia and xanthinuria. Here, we identified a patient whose plasma and urine uric acid levels were both extremely low and aimed to identify the pathogenic gene and verify its mechanism. Methods: Using next-generation sequencing (NGS), we detected a mutation in the human molybdenum cofactor sulfurase (MCSU) gene that may cause hypouricemia. We cultured L02 cells, knocked down MCSU with RNAi, and then detected the uric acid and MCSU concentrations, xanthine oxidase (XOD) and xanthine dehydrogenase (XDH) activity levels, and xanthine/hypoxanthine concentrations in cell lysates and culture supernatants. Results: The NGS results showed that the patient had a mutation in the human MCSU gene. The in vitro study showed that RNAi of MCSU caused the uric acid, human MCSU concentrations, the XOD and XDH activity levels among cellular proteins and culture supernatants to be extremely low relative to those of the control. However, the xanthine/hypoxanthine concentrations were much higher than those of the control. Conclusions: We strongly confirmed the pathogenicity of the human MCSU gene.